Functional characterization of missense mutations in severe methylenetetrahydrofolate reductase deficiency using a human expression system. Issue 2 (14th October 2016) - Burda, Patricie; Suormala, Terttu; Heuberger, Dorothea; Schäfer, Alexandra; Fowler, Brian; Froese, D. Sean; Baumgartner, Matthias R.
Abstract: 5, 10‐Methylenetetrahydrofolate reductase (MTHFR) catalyzes the NADPH‐dependent reduction of 5, 10‐methylenetetrahydrofolate to 5‐methyltetrahydrofolate using FAD as the cofactor. Severe MTHFR deficiency is the most common inborn error of folate metabolism, resulting in hyperhomocysteinemia and homocystinuria. Approximately 70 missense mutations have been described that cause severe MTHFR deficiency, however, in most cases their mechanism of dysfunction remains unclear. Few studies have investigated mutational specific defects; most of these assessing only activity levels from a handful of mutations using heterologous expression. Here, we report the in vitro expression of 22 severe MTHFR missense mutations and two known single nucleotide polymorphisms (p.Ala222Val, p.Thr653Met) in human fibroblasts. Significant reduction of MTHFR activity (<20 % of wild‐type) was observed for five mutant proteins that also had highly reduced protein levels on Western blot analysis. The remaining mutations produced a spectrum of enzyme activity levels ranging from 22–122 % of wild‐type, while the SNPs retained wild‐type‐like activity levels. We found increased thermolability for p.Ala222Val and seven disease‐causing mutations all located in the catalytic domain, three of which also showed FAD responsiveness in vitro. By contrast, six regulatory domain mutations and two mutations clustering around the linker region showed increased thermostability compared to wild‐type protein. Finally, we confirmed decreased affinity for NADPH in individual mutant enzymes, a result previously described in primary patient fibroblasts. Our expression study allows determination of significance of missense mutations in causing deleterious loss of MTHFR protein and activity, and is valuable in detection of aberrant kinetic parameters, but should not replace investigations in native material.